Formic Acid Dehydrogenation Catalysed by Tris(TPPTS)1 Ruthenium Species: Mechanism of the Initial "Fast" Cycle. Issue 11 (18th September 2014) - Thevenon, Arnaud; Frost‐Pennington, Ewan; Weijia, Gan; Dalebrook, Andrew F.; Laurenczy, Gábor
Abstract Water‐soluble ruthenium m‐triphenylphosphinetrisulfonate (TPPTS) complexes are excellent catalysts for formic acid dehydrogenation. Interestingly, the choice of metal catalyst precursor has a direct influence on initial activities. The reaction with hexaaquaruthenium(II) tosylate directly yields bisphosphine complexes in the presence of TPPTS and formic acid, whereas trisphosphine adducts are involved if the reaction starts with ruthenium(III) chloride. We present the results of a series of manometric and spectroscopic experiments that reveal the true nature of these highly active species, and subsequently propose a rational "fast" cycle mechanism explaining this peculiar activity profile.